Tradisi Carok dalam Hukum Pidana berbasis Pendekatan HolistikAntropologi Hukum - Surya Kusuma Wardana; Emy Handayani (Wijayakusuma Law Review, 2024)
The Carok tradition is an alternative dispute resolution in Madurese society, resolved through violence andin conflict with state law in Indonesia. Criminal Law can accommodate, regulate and respond to carokcultural values and their application which are contrary to criminal law in Indonesia, which is regulatedin the Criminal Code. The approach used in this writing is Holistic Legal Anthropology.